2017
DOI: 10.1111/cei.12946
|View full text |Cite
|
Sign up to set email alerts
|

Protective antibodies against Clostridium difficile are present in intravenous immunoglobulin and are retained in humans following its administration

Abstract: Summary The prevalence of serum antibodies against Clostridium difficile (CD) toxins A and B in healthy populations have prompted interest in evaluating the therapeutic activity of intravenous immunoglobulin (IVIg) in individuals experiencing severe or recurrent C. difficile infection (CDI). Despite some promising case reports, a definitive clinical role for IVIg in CDI remains unclear. Contradictory results may be attributed to a lack of consensus regarding optimal dose, timing of administration and patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Although intra-venous gamma globulins (IVGG) have been tested in many patients with CDI, the results are varied and make recommendation for use difficult ( O’Horo and Safdar, 2009 ; Diraviyam et al, 2016 ). Negm et al (2017) observed differences in TcdA neutralizing efficacy between three commercial immunoglobulin preparations as well as differences in level of specific IgG isotypes against C. difficile antigens.…”
Section: Passive Immunizations Targeting C Difficile mentioning
confidence: 85%
“…Although intra-venous gamma globulins (IVGG) have been tested in many patients with CDI, the results are varied and make recommendation for use difficult ( O’Horo and Safdar, 2009 ; Diraviyam et al, 2016 ). Negm et al (2017) observed differences in TcdA neutralizing efficacy between three commercial immunoglobulin preparations as well as differences in level of specific IgG isotypes against C. difficile antigens.…”
Section: Passive Immunizations Targeting C Difficile mentioning
confidence: 85%
“…While the identification of pathogen-specific antibodies is a cornerstone of microbiologic diagnostics, a commercial assay for the serological confirmation of ongoing CDI is lacking. Several investigators have developed tests to evaluate the host humoral immune response to infection (38-40). An association has also been demonstrated between the humoral immune response to CD and infectious course (21).…”
Section: Discussionmentioning
confidence: 99%
“…The approach of using specific IgY for prevention and treatment of CDI offers an alternative to current immunotherapies, which use intravenous administration of anti-TcdA and TcdB monoclonal human antibodies (Negm et al, 2017 ). To the best of our knowledge, there are no reported prophylactic therapies that target to prevent the initiation of CDI in a susceptible host by removing C. difficile spores from the host.…”
Section: Discussionmentioning
confidence: 99%